Gestational Weight Gain and Neonatal Biometry during the COVID-19 Pandemic: A Multicenter Observational Cohort - Abdelwahab, Mahmoud; Voest, Jessica A. de; Metz, Torri D.; Hughes, Brenna L.; Grobman, William A.; Saade, George R.; Manuck, Tracy A.; Longo, Monica; Simhan, Hyagriv N.; Rouse, Dwight J.; Mendez-Figueroa, Hector; Gyamfi-Bannerman, Cynthia; Bailit, Jennifer L.; Costantine, Maged M.; Sehdev, Harish M.; Tita, Alan T.N.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units Network, Bethesda, MD, United States (American Journal of Perinatology, 2024)
Objective This study aimed to test the hypothesis that being pregnant and delivering during the coronavirus disease 2019 (COVID-19) pandemic was associated with changes in gestational weight gain (GWG) or frequency of small- (SGA) or large-for-gestational-age (LGA) neonates.Study Design Secondary analysis of a multicenter observational cohort comparing pregnant people who delivered during the COVID-19 pandemic (June–December 2020) to people who delivered prior to the pandemic (March–December 2019). Those with multiple gestations, fetuses with major congenital anomalies, implausible GWG values, unavailable body mass index (BMI), or who were severe acute respiratory syndrome coronavirus-2-positive were excluded. The primary outcome was frequency of optimal recommended GWG based on prepregnancy BMI. Neonatal outcomes included birth weight, ponderal index, and frequency of SGA, LGA, and small head circumference for live births. Multivariable regression analysis was used to assess associations between exposure to the pandemic and outcomes.Results A total of 10,717 pregnant people were included in our analysis. A total of 4,225 pregnant people were exposed to the pandemic and 6,492 pregnant people delivered prior to the COVID-19 pandemic. Pregnant people exposed to the pandemic were older and more likely to have gestational diabetes. The frequency of appropriate GWG was 28.0% during the pandemic and 27.6% before the pandemic (adjusted odds ratio [aOR]: 1.02, 95% confidence interval [CI]: 0.93–1.11). Excessive GWG was more likely (54.9 vs. 53.1%; aOR: 1.08, 95% CI: 1.001–1.17), and inadequate GWG was less likely during the pandemic (17.0 vs. 19.3%; aOR: 0.86, 95% CI: 0.77–0.95). The frequency of SGA was 5.4% during the pandemic and 6.1% before the pandemic (aOR: 0.90, 95% CI: 0.76–1.06), and the frequency of LGA was 16.0% during the pandemic versus 15.0% before the pandemic (aOR: 1.06, 95% CI: 0.95–1.18). Other neonatal outcomes including birth weight percentile (62.1 [35.8–83.2] vs. 60.2 [34.4–82.2]; adjusted mean difference (aMD) = 1.50, 95% CI: −0.28 to 3.29), ponderal index (2.6 g/cm3 [2.4–2.8] in both groups; aMD = 0.01, 95% CI: 0.00–0.02), and small head circumference for livebirths (<10th percentile [8.2 vs. 8.1%; aOR: 1.03, 95% CI: 0.89–1.19], <3rd percentile [3.5 vs. 3.1%; aOR: 1.16, 95% CI: 0.93–1.44]) were similar between groups as well.Conclusion Being pregnant and delivering during the COVID-19 pandemic was associated with a higher likelihood of excessive GWG and a lower likelihood of inadequate GWG.Key Points
Keywords: COVID-19 in pregnancy; gestational weight gain; neonatal biometry; quarantine